Human Adenovirus 7-Associated Hemophagocytic Lymphohistiocytosis-like Illness: Clinical and Virological Characteristics in a Cluster of Five Pediatric Cases. (31st August 2020) - Otto, William R; Behrens, Edward M; Teachey, David T; Lamson, Daryl M; Barrett, David M; Bassiri, Hamid; Lambert, Michelle P; Mount, Suzanne; Petrosa, Whitney L; Romberg, Neil; Sullivan, Kathleen E; Topjian, Alexis A; et al.
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition of immune dysregulation. Children often suffer from primary genetic forms of HLH, which can be triggered by infection. Others suffer from secondary HLH as a complication of infection, malignancy, or rheumatologic disease. Identifying the exact cause of HLH is crucial, as definitive treatment for primary disease is hematopoietic stem cell transplant. Adenoviruses have been associated with HLH but molecular epidemiology data are lacking. Methods: We describe the clinical and virologic characteristics of 5 children admitted with adenovirus infection during 2018–2019 who developed HLH or HLH-like illness. Detailed virologic studies, including virus isolation and comprehensive molecular typing were performed. Results: All patients recovered; clinical management varied but included immunomodulating and antiviral therapies. A genetic predisposition for HLH was not identified in any patient. Adenovirus isolates were recovered from 4/5 cases; all were identified as genomic variant 7d. Adenovirus type 7 DNA was detected in the fifth case. Phylogenetic analysis of genome sequences identified 2 clusters—1 related to strains implicated in 2016–2017 outbreaks in Pennsylvania and New Jersey, the other related to a 2009 Chinese strain. Conclusions: It can be challenging to determine whether HLH is the result of an infectious pathogen alone or genetic predisposition triggered by an infection. We describe 5 children from the same center presenting with an HLH-like illness after onset of adenovirus type 7 infection. None of the patients were found to have a genetic predisposition to HLH. These findings suggest that adenovirus 7 infection alone can result in HLH. Abstract : We describe clinical and virologic characteristics of five children with hemophagocytic lymphohistiocytosis (HLH) and hyperinflammation after infection with adenovirus 7d. These findings raise interesting questions regarding the contribution of the pathogen versus the host in HLH in young children.